Performance Analysis of an IPMSM When Applying Heavy Rare-Earth-Free NdFeB PMs - Ogrizek, Pavel; Garmut, Mitja; Petrun, Martin (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The pursuit of greener technologies has prompted research into alternatives to heavy rare-earth (HRE) permanent magnet (PM) materials in electric machines, notably Interior Permanent Magnet Synchronous Machines (IPMSMs). This study examines how an IPMSM performs with HRE-free PMs, aiming to reduce environmental impact and costs linked to HRE material use. Using a two-dimensional transient Finite Element Method (2D-FEM) IPMSM model in Ansys Maxwell 2D, torque and power characteristics across different speed ranges for IPMSM models with two HRE-free PM materials and traditional HRE PMs were compared. Scaling law was implemented on HRE-free PM models to maintain the maximum torque.